2013
DOI: 10.1155/2013/583786
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Risk of Cancer

Abstract: Diabetes and cancer represent two complex, diverse, chronic, and potentially fatal diseases. Cancer is the second leading cause of death, while diabetes is the seventh leading cause of death with the latter still likely underreported. There is a growing body of evidence published in recent years that suggest substantial increase in cancer incidence in diabetic patients. The worldwide prevalence of diabetes was estimated to rise from 171 million in 2000 to 366 million in 2030. About 26.9% of all people over 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 199 publications
(215 reference statements)
2
105
0
1
Order By: Relevance
“…Higher relative risks of liver, pancreatic, or endometrial cancer have been reported in diabetic patients, whereas the increase of relative risks of breast, bladder, colorectal, kidney, and biliary neoplasms is less evident; moreover, the relative risk of prostate cancer seems even lower in diabetic patients [2,76].…”
Section: Discussionmentioning
confidence: 97%
“…Higher relative risks of liver, pancreatic, or endometrial cancer have been reported in diabetic patients, whereas the increase of relative risks of breast, bladder, colorectal, kidney, and biliary neoplasms is less evident; moreover, the relative risk of prostate cancer seems even lower in diabetic patients [2,76].…”
Section: Discussionmentioning
confidence: 97%
“…According to several meta-analyses, an increased frequency of malignancies in diabetic patients has been attributed to various general and local mechanisms (1,3,4,10,12).…”
Section: Incidence Of Different Types Of Cancer Among Diabetic Patientsmentioning
confidence: 99%
“…The hepatocellular carcinoma (HCC) incidence is higher in those with T2DM in the two genders, with a greater risk in males and in those with concomitant hepatitis C virus (HCV) infection: As the majority of epidemiological studies indicate a 2-3-fold increase in liver cancer in diabetic patients, it is feasible that diabetes may also act synergistically with other well-established risk factors for HCC, including hepatitis B virus and HCV infection, non-alcoholic fatty liver disease (also considered as hepatic manifestation of diabetes and metabolic syndrome), non-alcoholic steatohepatitis and chronic alcohol consumption leading to steatosis and cirrhosis (1,3,16). In particular, the mitogenic pathway of insulin is unlikely to be involved considering that healthy liver cells, due to insulin secretion bursts in the portal circulatory system, are physiologically exposed to higher insulin concentrations compared to other peripheral tissues (10), above all in the insulin-resistant hyperinsulinemic type 2 states (whereas in insulin-deficient T1DM individuals treated with exogenous insulin, the liver is exposed to the same insulin levels as the other organs).…”
Section: Incidence Of Different Types Of Cancer Among Diabetic Patientsmentioning
confidence: 99%
See 2 more Smart Citations